2015
DOI: 10.1016/j.jet.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Contract design and non-cooperative renegotiation

Abstract: We study a contract design setting in which the contracting parties cannot commit not to renegotiate previous contract agreements. In particular, we characterize the outcome functions that are implementable for an uninformed principal and an informed agent if, having observed the agent's contract choice, the principal can offer a new menu of contracts in its place. An outcome function can be implemented in this setting if and only if it is optimal for the principal for some belief over agent types which is mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The only difference from Section 3 is that one must replace the "discrete" incentive constraints by continuous ones. Notice that system (( d) σ * ) is incentive compatible if 15 This logic is somewhat similar to Evans and Reiche (2015), where it is shown that if one considers a fixed renegotiation length, the optimal IC mechanism can be implemented. Thus, the fact that the mechanism can be renegotiated does not matter.…”
Section: A1 Optimal Ic Systemmentioning
confidence: 91%
See 1 more Smart Citation
“…The only difference from Section 3 is that one must replace the "discrete" incentive constraints by continuous ones. Notice that system (( d) σ * ) is incentive compatible if 15 This logic is somewhat similar to Evans and Reiche (2015), where it is shown that if one considers a fixed renegotiation length, the optimal IC mechanism can be implemented. Thus, the fact that the mechanism can be renegotiated does not matter.…”
Section: A1 Optimal Ic Systemmentioning
confidence: 91%
“… This logic is somewhat similar to Evans and Reiche (), where it is shown that if one considers a fixed renegotiation length, the optimal IC mechanism can be implemented. Thus, the fact that the mechanism can be renegotiated does not matter.…”
mentioning
confidence: 96%
“…She could simply pass on n − 1 opportunities and then propose the optimal contracts. Evans and Reiche (2015) assume that after an initial mechanism is played, the principal can offer a new mechanism and the agent may choose whether to retain the outcome of the original mechanism or to participate in the new mechanism. They assume that there is no friction in-between the mechanism proposals, as do we.…”
mentioning
confidence: 99%
“…Evans and Reiche (2015), for example, assume that after an initial mechanism is played, the principal can offer a new mechanism and the agent may choose whether to retain the outcome of the original mechanism or to participate in the new mechanism. They assume that there is no friction in-between the mechanism proposals, as do we.…”
mentioning
confidence: 99%
“…In this setting, the optimal mechanism from the point of view of the principal is easy to implement if she proposes the null mechanism in the first round and the optimal mechanism in the second round. What makes the analysis of Evans and Reiche (2015) interesting is the fact that they allow a third party whose goals are not aligned with the principal to propose the initial mechanism. This third party must then take into account that the outcome of the mechanism may be subject to renegotiation.…”
mentioning
confidence: 99%